An Abundance of Riches: Cross-Task Comparisons of Semantic Richness Effects in Visual Word Recognition - Yap, Melvin J.; Pexman, Penny M.; Wellsby, Michele; Hargreaves, Ian S.; Huff, Mark (Frontiers in Human Neuroscience, 2012)
There is considerable evidence (e.g., Pexman, Hargreaves, Siakaluk, Bodner, & Pope, 2008) that semantically rich words, which are associated with relatively more semantic information, are recognized faster across different lexical processing tasks. The present study extends this earlier work by providing the most comprehensive evaluation to date of semantic richness effects on visual word recognition performance. Specifically, using regression analyses to control for the influence of correlated lexical variables, we considered the impact of contextual dispersion, number of features, number of senses, semantic neighborhood density, imageability, and body-object interaction across five visual word recognition tasks: standard lexical decision, go/no-go lexical decision, speeded pronunciation, semantic classification, and progressive demasking. Semantic richness effects could be reliably detected in all tasks of lexical processing, indicating that semantic representations, particularly their imaginal and featural aspects, play a fundamental role in visual word recognition. However, there was also evidence that the strength of certain richness effects could be flexibly and adaptively modulated by task demands, consistent with an intriguing interplay between task-specific mechanisms and differentiated semantic processing.